Can Society 5.0 inspire youth to build a resilient agro-based economy? - Mahjom, Nurhanie; Abdul Razak, Azila; Muhammad, Fidlizan; Mohd Hussin , Mohd Yahya; Ismail, Zuriadah (Journal of Islamic, Social, Economics and Development, 2025)
The advent of Society 5.0 marks a transformative phase in which technology and human ingenuity converge to address socio-economic challenges. Within this context, revitalising the agro-based economy through digital innovation has become imperative. However, persistent youth reluctance to participate in agriculture poses a serious threat to the resilience and sustainability of national food systems. This paper explores how the core principles of Society 5.0, namely human-centred innovation, digital integration, and smart solutions, can serve as catalysts to reimagine agriculture as a modern, attractive, and future-oriented sector. Supported by empirical evidence, the discussion analyzes how income insecurity, limited access to technology, and negative social perceptions hinder youth engagement. The findings suggest that strategic alignment between digital transformation, inclusive policy frameworks, and youth empowerment initiatives can redefine the agro-based economy as a viable and progressive domain. Ultimately, embedding Society 5.0 principles in agricultural development is essential to cultivate a resilient, innovative, and food-secure future.